Using discrete multi-physics for detailed exploration of hydrodynamics in an in vitro colon system. (1st February 2017) - Alexiadis, A.; Stamatopoulos, K.; Wen, W.; Batchelor, H.K.; Bakalis, S.; Barigou, M.; Simmons, M.J.H.
Abstract: We developed a mathematical model that describes the motion of viscous fluids in the partially-filled colon caused by the periodic contractions of flexible walls (peristalsis). In-vitro data are used to validate the model. The model is then used to identify two fundamental mechanisms of mass transport: the surfing mode and the pouring mode. The first mechanism is faster, but only involves the surface of the liquid. The second mechanism causes deeper mixing, and appears to be the main transport mechanism. Based on the gained understanding, we propose a series of measures that can improve the reliability of in-vitro models. The tracer in PET-like experiments, in particular, should not be injected in the first pocket, and its viscosity should be as close as possible to that of the fluid. If these conditions are not met, the dynamics of the tracer and the fluid diverge, compromising the accuracy of the in-vitro data. Highlights: A computational model of the colon is proposed. The computational model is validated with results from an in-vitro model. The major fluid dynamics features of convective transport in the colon are identified and discussed. On the basis of the gained understanding, suggestions for improving the in-vitro model are made.